Health Education Related Nutrition Pattern to Increase Quality of Life of Type 2 DM Patients - Jaka Pradika; Kharisma Pratama; Cau Kim Jiu; Wuriani Wuriani; Usman Usman; Yenni Lukita; Syahid Amrullah (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Diabetes Mellitus (DM) is a non-communicable disease whose prevalence is increasing every year in the world, including in Indonesia. DM patients are very susceptible to ulcers caused by uncontrolled blood sugar due to the wrong diet. The low level of knowledge related to eating patterns is a problem that must be addressed so that the incidence can be suppressed. In this case, education is needed to increase the understanding of patients and families in terms of eating patterns. The right diet or eating pattern will certainly be one aspect in improving the quality of life of type 2 DM patients. The purpose of this activity is to increase knowledge, especially in the right diet in type 2 DM patients, it is hoped that it can improve the quality of life of type 2 DM patients by controlling blood sugar due to a good diet. The method used is to provide counseling with lecture, discussion and question and answer methods. The targets of this community service program are patients suffering from type 2 DM and their families in Sungai Ambangah village, Kubu Raya district. The results of this activity indicate that the effectiveness of counseling has an effect on increasing knowledge of type 2 DM patients and their families. This can be seen from the evaluation results that people with type 2 DM and their families understand the right diet for people with DM.